PUBLIC PERCEPTION OF JOURNALISTIC PROFESSION IN DAYAH BARO VILLAGE, KRUENG SABEE DISTRICT, ACEH JAYA REGENCY - Abshar, Nurul; Mirdad, Jamal (Transpublika Publisher, 2022)
perceptions from the public regarding the journalist profession. In conducting the research, The author uses a qualitative approach with a descriptive approach, and the data collection of this survey was conducted through observation, interviews, and documentation. The results of this study are public perceptions of Dayah Baro Village, Krueng Sabee District, Aceh Jaya Regency towards the journalist profession is positive, namely with journalists being able to provide the latest information and facilitate public access to information and negative, namely sometimes journalists make sensational news with hard titles but when read the contents do not match the title, besides that the journalist profession creates negative perceptions from the public due to the presence of individuals who do not reflect their journalistic attitude, one of which is not paying attention to the existing regulations in the village where news coverage is carried out, while the image of the journalist profession in Aceh Jaya assumes that journalists are in the field of work. which is noble for everyone because it can be a mouthpiece between the community and the government and vice versa.